Contemporary view on thread lifting: Histological and anatomical approaches - Olga B. Borzykh; Elena I. Karpova; Natalia A. Shnayder; Olga M. Demina (Russian Open Medical Journal)
Currently, thread lifting in aesthetic facial rejuvenation is not the top priority, but nevertheless its popularity continues to gain momentum. In connection with increasing popularity, the number of issues related to thread lifting and its undesirable side effects also increases. In this publication, an analysis of Russian and international databases was carried out, including MedLine, PubMed, elibrary.ru, Wiley Online Library, Web of Science, over the period from 2010 to 2020 (10 years). In the search, the following keywords were used both in Russian and English: threads, thread lifting, rhytidoplasty, face rejuvenation, face lift, cog threads, Aptos, suture material. As a result, of all available publications, 51 articles were left for further analysis, on the basis of which the nuances of thread classification, histological changes in tissues in response to thread implantation, along with anatomical basics and features during the procedure of thread lifting were analyzed. The effectiveness and duration of the thread lifting effect is still subject to debate. Hence, sometimes, it is possible to identify the duration of the effect in the same study ranging from 1 month to 2 years. Despite the long history of thread lifting, there are still unresolved issues that need to be covered.